Handbook of research on machine and deep learning applications for cyber security - Ganapathi, Padmavathi, 1964; Shanmugapriya, D., 1978 (A volume in the advances in information security, privacy, and ethics (AISPE) book series, 2020)
"This book explores the use of machine learning and deep learning applications in the areas of cyber security and cyber-attack handling mechanisms"